Omicron-BA.1 Dispersion Rates in Mexico Varied According to the Regional Epidemic Patterns and the Diversity of Local Delta Subvariants - Zárate, Selene; Taboada, Blanca; Rosales-Rivera, Mauricio; García-López, Rodrigo; Muñoz-Medina, José Esteban; Sanchez-Flores, Alejandro; Herrera-Estrella, Alfredo; Gómez-Gil, Bruno; Selem Mojica, Nelly; Salas-Lais, Angel Gustavo; Vazquez-Perez, Joel Armando; Cabrera-Gaytán, David Alejandro; et al. (Viruses, 2023)
Purpose: The Omicron subvariant BA.1 of SARS-CoV-2 was first detected in November 2021 and quickly spread worldwide, displacing the Delta variant. In this work, a characterization of the spread of this variant in Mexico is presented. Methods: The time to fixation of BA.1, the diversity of Delta sublineages, the population density, and the level of virus circulation during the inter-wave interval were determined to analyze differences in BA.1 spread. Results: BA.1 began spreading during the first week of December 2021 and became dominant in the next three weeks, causing the fourth COVID-19 epidemiological surge in Mexico. Unlike previous variants, BA.1 did not exhibit a geographically distinct circulation pattern. However, a regional difference in the speed of the replacement of the Delta variant was observed. Conclusions: Viral diversity and the relative abundance of the virus in a particular area around the time of the introduction of a new lineage seem to have influenced the spread dynamics, in addition to population density. Nonetheless, if there is a significant difference in the fitness of the variants, or if the time allowed for the competition is sufficiently long, it seems the fitter virus will eventually become dominant, as observed in the eventual dominance of the BA.1.x variant in Mexico.